Seed germination and ultra structural changes in oil palm (Elaeis guineensis) hybrid seed influenced by heat treatments - MURUGESAN, P; RAVICHANDRAN, G; SHAREEF, M (The Indian Journal of Agricultural Sciences, 2015)
Seed dormancy in oil palm (Elaeis guineensis Jacq.) is considered as one of the major causes for low and erratic germination. Oil palm hybrid seeds (dura × pisifera) were subjected to heat treatment for 0, 10, 20, 30, 40, 50, 60, 70, 80 and 90 days in a heating room at 39 + 1ºC and germination response, ultrastructural changes in embryo, endosperm and operculum structures were observed. The results revealed that seed heating for 50, 60 and 70 days and incubation in germination room (25 to 27 ºC) resulted in germination of 90.4, 93.6 and 94.8%, respectively. Heating of seeds for 0, 10 and 20 days had no effect on germination. Structural changes of dormant and germinating seeds were investigated through microtome sectioning and Scanning Electron Microscope (SEM). Endosperm above the embryo is demarcated by several layers of small cells. During the break of seed dormancy, endosperm cleaves in the micropylar region through the small cells. Enlargement of embryo facilitates the dislocation of the operculum during the germination. It is confirmed that heat treatment for 60 to 70 days to be optimum for obtaining maximum oil palm seed germination. Nevertheless, heating oil palm seeds at 50oC is recommended for maximum germination in a short time.